PENGHAWAAN ALAMI DAN KENYAMANAN TERMAL PADA MASJID KHALID AL-NAQOBI - Reza Alvi Yulita; Gagoek Hardiman; Erni Setyowati (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2023)
Abstract: The mosque is a place for Muslims to worship. As a place of worship, of course the user's comfort while worshiping in the mosque is very important so that users can worship solemnly. The Khalid Al-Naqobi Mosque is one of the mosques in the program to build 100 waqf mosques from Qatar whose construction is being managed by PBNU in Indonesia. The waqf mosque will begin to be built at the end of 2021 and will be built in various regencies and cities, however, during its construction, the management has determined a blue print design and materials to be used in almost all waqf mosque constructions with different existing conditions. So it is likely that the conditioning factors in the building are not considered. The purpose of this study was to evaluate whether the design of the Khalid Al-Naqobi mosque was able to overcome room conditioning in realizing the thermal comfort of its users. The results of this observation can be used as a consideration in designing mosques with natural ventilation.Keyword: Mosque, Architecture, Thermal ComfortAbstrak: Masjid merupakan tempat umat muslim untuk beribadah. Sebagai tempat beribadah tentunya kenyamanan pengguna saat beribadah di dalam masjid sangatlah penting agar pengguna bisa beribadah dengan khusuk. Masjid Khalid Al-Naqobi merupakan salah satu masjid dari program pembangunan 100 masjid wakaf dari Qatar yang dikelola pembangunannya oleh PBNU di Indonesia. Masjid wakaf ini mulai di bangun pada akhir tahun 2021 dan dibangun di berbagai kabupaten maupun kota, namun dalam pembangunannya pengelola sudah menentukan satu desain blue print serta material-material yang digunakan untuk diterapkan hampir di semua pembangunan masjid wakaf dengan kondisi eksisting yang berbeda-beda. Sehingga besar kemungkinan faktor-faktor pengkondisian dalam bangunan kurang diperhatikan Tujuan dari penelitian ini adalah untuk mengevaluasi apakah desain masjid Khalid Al-Naqobi ini mampu mengatasi pengkondisian ruangan dalam mewujudkan kenyamanan termal penggunanya. Hasil dari pengamatan ini dapat digunakan sebagai pertimbangan dalam perancangan masjid dengan penghawaan alami.Kata Kunci: Â Masjid, Arsitektur, Kenyamanan termal.Â